Visiting the Secondary Social Studies Curriculum in Perilous Times - Gil, Tyrone Ogaro (International Journal Pedagogy of Social Studies, 2022)
In such perilous times and unabated marginalization, it is pivotal to pay a visit to the secondary social studies curriculum. This article will decipher the status of the implementation and academic location of secondary social studies in the emergency curriculum (MELCs). This study adopted the multiple case study design, where several units of analysis had been examined to elucidate raw data from each unit. Data collection in this study includes: Focus Group Discussion and literature tudies, The results of the analysis of data will be presented in the form of themes accompanied by theories and literature studies. Through a careful examination of the Most Essential Learning Competencies (MELCs), developed self-learning modules (SLM), and field notes collected from the curriculum gatekeepers (secondary social studies teachers), the researcher was able to generate exhaustive and perplexing findings in remote teaching- learning of social studies.